Lernwelt Hochschule 2030 Konzepte und Strategien für eine zukünftige Entwicklung - Stang, Richard; Becker, Alexandra (Lernwelten, 2022)
Tertiary institutions are facing expectations of change on all sides resulting from the challenges of new public management, the Bologna Process, a shift from teaching to learning, competence orientation, and societal transformation. To master this transformation, all actors must work together. This volume presents various perspectives on management dimensions and innovative approaches toward further developing the tertiary learning environment.